How Cortisol Reactivity Influences Prosocial Decision-Making: The Moderating Role of Sex and Empathic Concern - Zhang, Qionghan; Ma, Jianhong; Nater, Urs M. (Frontiers in Human Neuroscience, 2019)
The fight and flight theory and the tend-and-befriend theory suggest two opposite behavioral stress responses, and heterogeneous research results revealed the importance of taking sex into account. The experiment was designed to investigate the effect of stress-related cortisol reactivity on subsequent prosocial decision-making behaviors, and the moderating role of sex and empathic concern in the process. Sixty-one healthy students (34 women, 27 men) underwent the Trier Social Stress Test for Groups (TSST-G) or the control condition. Subsequently, participants completed three economic tasks ─ the dictator game, the ultimatum game, and the third-party compensation game. Statistical analyses revealed a significant main effect of cortisol reactivity on individuals’ third-party compensation behaviorssex. A sex-specific effect of stress-related cortisol change on prosocial behaviors was found, with men behaved more generously in the dictator game as stress-related cortisol reactivity increased. Furthermore, the level of empathic concern was found to moderate the association between stress-related cortisol change and prosocial behaviors, that individuals with a low level of empathic concern reported more generosity and third-party compensation behaviors. Overall, the present study contributes to a better understanding of the behavioral stress responses, that individuals whose hypothalamic-pituitary-adrenal axis are highly activated in response to stress would exhibit tend-and-befriend responses, but only among men and those with a low level of empathic concern.